2013
DOI: 10.1177/0743558413480836
|View full text |Cite
|
Sign up to set email alerts
|

“I’m Not Going to Become No Rapper”

Abstract: Few studies examine how the macro context shapes ethnic or racial identity development during early adolescence. This analysis draws on interview data from 40 African American, Chinese American, Dominican American, and European American middle school students (6th through 8th grade) to explore how stereotypes inform adolescents' ethnic and racial identities. Findings revealed that stereotypes about race and ethnicity intersected with those about gender, sexuality, social class, and/or nationality and these int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 55 publications
4
66
0
Order By: Relevance
“…Evidence of accommodation is also revealed in identity development when boys simultaneously accommodate to and resist dominant ideologies by claiming "not to be a stereotype," but implicitly and explicitly suggesting that those same stereotypes apply to other members of their own racial-ethnic group [Way & Rogers, 2014;Way, Hernández, Rogers, & Hughes, 2013;Way et al, 2008]. In Rogers' study, such boys effectively describe themselves as an exception to the stereotype [Rogers, 2018b;Rogers & Way, 2016].…”
Section: Resistance and Accommodation In Identity Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of accommodation is also revealed in identity development when boys simultaneously accommodate to and resist dominant ideologies by claiming "not to be a stereotype," but implicitly and explicitly suggesting that those same stereotypes apply to other members of their own racial-ethnic group [Way & Rogers, 2014;Way, Hernández, Rogers, & Hughes, 2013;Way et al, 2008]. In Rogers' study, such boys effectively describe themselves as an exception to the stereotype [Rogers, 2018b;Rogers & Way, 2016].…”
Section: Resistance and Accommodation In Identity Developmentmentioning
confidence: 99%
“…Data from Way's studies on friendships and identity development entail longitudinal mixed-method studies in which she follows boys (and girls) from early to late adolescence and have been funded primarily by the National Science Foundation and the William T. Grant Foundation. They have been conducted in coeducational public middle and high schools in the Northeast [see Way, 2011;Way et al, 2008Way et al, , 2013. Data collection included surveys, classroom observations, and in-depth interviews.…”
Section: Our Research Studiesmentioning
confidence: 99%
“…As adolescents become more independent and spend more time outside of the home, they might be faced with the need to evaluate who they are. Exposure to new people and settings that might treat them unfairly or, at the very least, judge or stereotype them in ethnic or race-related ways could drive adolescents' cultural identity development as well as instigate conversations about ethnicity or race between adolescents and parents or other socialization agents (Way, Hern andez, Rogers, & Hughes, 2013). In particular, social contexts that have been understudied in the literature but can be seen to have gained salience in adolescents' lives, both in terms of normative developmental influences as well as through increased societal emphasis over time, include extracurricular settings (i.e., sports, work) and social media contexts.…”
Section: Res and Adolescents' Contexts Of Developmentmentioning
confidence: 99%
“…Scholars have also written about how the school context and social stereotypes related to social identity impact how adolescents construct their identities (Fordham, 1996;Fordham & Ogbu, 1986;Spencer, 1995;Way, Hernandez, Rogers, & Hughes, 2013). In particular, researchers have found that the intersection of race and gender stereotypes are connected to harsh discipline for Black adolescent males and promote a widespread belief that they are deficient in terms of academic achievement (Way, 2011), which can dampen self-concept.…”
Section: Gender Roles and Self-concept (General And School)mentioning
confidence: 99%